1995
DOI: 10.1159/000288953
|View full text |Cite
|
Sign up to set email alerts
|

Stress in Middle-Aged Women: Influence of Type A Behavior and Narcissism

Abstract: The authors examined (1) strength of stress, (2) awareness of stress, and (3) influence of type A behavior and narcissistic personality on stress and its related factors in a sample of 500 middle-aged women. Compared to 400 middle-aged working men, the women scored lower on the type A and coping scales, suggesting the possibility that women with high scores on type A behavior cope better with stress. Moreover, type A behavior in women was related to narcissistic personality. The strength of stressors and stres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 8 publications
1
3
0
Order By: Relevance
“…Similarly, we found that greater adaptive narcissism was associated with fewer depressive symptoms, sleep problems and stress at home, whereas greater maladaptive narcissism was associated with higher work stress, both in the bivariate and adjusted analysis. These observations concur with previous studies further supporting the notion that narcissism is related to a range of health-related outcomes2, 3, 4, 5, 6, 7, 8 ) . Nonetheless, the investigation of and observed link between narcissism and personal burnout was a novelty and primary focus of our study.…”
Section: Resultssupporting
confidence: 92%
See 2 more Smart Citations
“…Similarly, we found that greater adaptive narcissism was associated with fewer depressive symptoms, sleep problems and stress at home, whereas greater maladaptive narcissism was associated with higher work stress, both in the bivariate and adjusted analysis. These observations concur with previous studies further supporting the notion that narcissism is related to a range of health-related outcomes2, 3, 4, 5, 6, 7, 8 ) . Nonetheless, the investigation of and observed link between narcissism and personal burnout was a novelty and primary focus of our study.…”
Section: Resultssupporting
confidence: 92%
“…Narcissism has been related to an array of personal and occupational outcomes2 ) , including perceived stress3, 4 ) , depression4, 5 ) , sleep quality4 ) , counterproductive work behavior6 ) , workaholism7 ) , and work stress8 ) , although its relation to burnout in a non-clinical context has not been scrutinized4 ) . Based on clinical experience and theoretical grounds, narcissistic personality features might also increase the risk of burnout, although empirical evidence of any such relationship is only emerging4 ) .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…What can be understood from this relationship between dominance and somatization? Some assumptions we would like to make here are that since the dominance personality trait is forceful – an assertive personality akin to a Type A – it has been found to be related to a narcissistic personality 48. It may therefore be speculated that sociocultural influences have a role to play, particularly among the Thai elderly, with regard to the dominance personality trait.…”
Section: Discussionmentioning
confidence: 99%